En Route to a Chiral Melanin: The Dynamic “From-Imprinted-to-Template” Supramolecular Role of Porphyrin Hetero-Aggregates During the Oxidative Polymerization of L-DOPA - Gaeta, Massimiliano; Randazzo, Rosalba; Villari, Valentina; Micali, Norberto; Pezzella, Alessandro; Purrello, Roberto; d'Ischia, Marco; D'Urso, Alessandro (Frontiers in Chemistry, 2020)
Chiral porphyrin hetero-aggregates, produced from meso-tetrakis(4-N-methylpyridyl) porphyrin, H2T4 and copper(II) meso-tetrakis(4-sulfonatophenyl)porphyrin, CuTPPS by an imprinting effect in the presence of L-DOPA, are shown herein to serve as templates for the generation of chiral structures during the oxidative conversion of the amino acid to melanin. This remarkable phenomenon is suggested to involve the initial role of L-DOPA and related chiral intermediates like dopachrome as templates for the production of chiral porphyrin aggregates. When the entire chiral pool from DOPA is lost, chiral porphyrin hetero-aggregate would elicit axially chiral oligomer formation from 5,6-dihydroxyindole intermediates in the later stages of melanin synthesis. These results, if corroborated by further studies, may open unprecedented perspectives for efficient strategies of asymmetric melanin synthesis with potential biological and technological applications.